Prime indicators of current teaching methodologies and students’ perceptions in quantum physics - Pascasie Nyirahabimana; Evariste Minani; Mathias Nduwingoma; Imelda Kemeza (International Journal of Evaluation and Research in Education (IJERE), 2022)
With the growing revolution in the education system, imparting quality education has become a priority for instructors and students in any educational institution. The challenge grows high when it comes to teaching advanced subjects like quantum physics. The present study considered the case study of the University of Rwanda College of Education. It investigated the impact of current teaching methodologies and teaching staff and students’ perceptions in quantum physics for a quality knowledge delivery system. It employed a quantitative method of data collection. About 300 students and ten lecturers participated in this study. Data obtained from this study were analyzed using descriptive quantitative analysis. Students suggested that multimedia tools in teaching and learning quantum physics can improve the understanding of concepts and help solve complex mathematical problems in quantum physics. Likewise, the teaching staff finds quantum physics more comprehensive and effective when appropriate multimedia tools are used. The investigation outcome is meant multimedia utilization can improve quantum physics’ teaching and learning experience at Rwanda high educational institutions.